2020
DOI: 10.1039/d0cp03197f
|View full text |Cite
|
Sign up to set email alerts
|

IR–VUV spectroscopy of pyridine dimers, trimers and pyridine–ammonia complexes in a supersonic jet

Abstract: The infrared spectra of the C-H stretching vibrations of pyridine, its dimer and trimer, and the N-H stretching vibrations of (pyridine)m-(NH3)n complexes were investigated with infrared (IR) - vacuum ultraviolet...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 77 publications
11
64
1
Order By: Relevance
“…However, investigations on similar systems such as pyridine, bromo-benzene, chloro-benzene, fluorophenylacetylene, or benzene clusters have been performed. 17,21,26,27,29,30 The investigations on these systems have been limited to dimer, trimer and tetramer except for benzene clusters for which larger sized clusters have been reported. 18,19 At the MP2/6-31+ +G(d,p) level of theory, Mahadevi et al 18 have reported the structures of the benzene clusters from dimer to octamer.…”
Section: Structures and Relative Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…However, investigations on similar systems such as pyridine, bromo-benzene, chloro-benzene, fluorophenylacetylene, or benzene clusters have been performed. 17,21,26,27,29,30 The investigations on these systems have been limited to dimer, trimer and tetramer except for benzene clusters for which larger sized clusters have been reported. 18,19 At the MP2/6-31+ +G(d,p) level of theory, Mahadevi et al 18 have reported the structures of the benzene clusters from dimer to octamer.…”
Section: Structures and Relative Stabilitymentioning
confidence: 99%
“…19 In addition to benzene, a few other systems similar to thiophene have been investigated using different levels of theory. [26][27][28][29][30] Reid and coworkers 26,27 have investigated the bromo-benzene dimer and the chloro-benzene dimer at the M06-2X/aug-cc-pVDZ level of theory. They have reported that the stacking/sandwich configuration is the most stable configuration of the chloro-benzene dimer and the bromo-benzene dimer in agreement with the results on benzene dimer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kuo and coworkers succeeded in analyzing F-R of the X H stretching vibration by using ab initio anharmonic algorithms using reduced-dimensional potential energy surfaces (PESs) up to CCSD(T)/aug-cc-pVTZ level of theory. [7,[13][14][15][16][17][18][19] It is well known that many of the IR spectra in the C H stretching region of aromatic molecules show very complicated features due to F-R. For example, benzene exhibits three absorption bands in the 3,020-3,130 cm À1 region due to F-R between an IR active C H stretching vibration (ν 20 ) and the combination bands of C H bending vibrations. [20,21] For the mono-substituted benzene, toluene exhibits more than nine bands [22] in the aromatic C H stretching vibration region, and phenol exhibits more than 15 bands in the C H stretching region.…”
Section: Introductionmentioning
confidence: 99%